The clinical profiles and outcomes of Hypertrophic Cardiomyopathy in Sarawak: A population-based descriptive study - Esteban Yu Hern, Chin; Oon, Yen Yee; Chung, Bui Khiong; Ling, Hwei Sung; Julian Wei Ee, Tong; Cheng Foong, Cheah; Andy Tze Yang, Ko; Chiang, Kit Hou; Leong, Lai Kuan; Khor, How Kiat; Pang, Ing Xiang; Chow, Han Bing; et al. (Elsevier B.V., 2024)
Hypertrophic Cardiomyopathy (HCM) is a genetic disorder associated with significant morbidity and mortality. Regional and local data are lacking despite extensive studies and documentations worldwide